Air-layering of Chilgoza (Pinus gerardiana Wall.) - Chandra, J. P.; Mehindru, J. L. (Indian Forester, 1976)
Results of study on air-layering of Chilgoza pine branches are roported. The application of Seradix B-3 induced rooting in twenty percent of the air-layers, while air-layers without the application of Seradix did not root.